2021
DOI: 10.1016/j.jiac.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with viral clearance periods from patients with COVID-19: A retrospective observational cohort study

Abstract: Introduction: Knowledge is limited on the virologic course of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, particularly the time taken for viral clearance and the optimal time to discontinue isolation. This study aims to identify the clinical and demographic factors influencing the time taken for viral clearance in patients with COVID-19 to determine the optimal isolation period. Methods: This two-center retrospective observational cohort study was conducted between March 1 and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Our study revealed that advanced age was associated with an increased risk of prolonged time to viral clearance, which is consistent with previous studies [ 19 , 22 , 23 ]. This could be attributed to the decline of T cell functions and proliferation with increasing age resulting in decreased control of viral replication and viral clearance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed that advanced age was associated with an increased risk of prolonged time to viral clearance, which is consistent with previous studies [ 19 , 22 , 23 ]. This could be attributed to the decline of T cell functions and proliferation with increasing age resulting in decreased control of viral replication and viral clearance.…”
Section: Discussionsupporting
confidence: 93%
“…In Xu et al's study [11,p.799–806], the severity of COVID-19 at admission was significantly associated with prolonged viral shedding. Time to viral clearance was also shorter among patients with mild symptoms compared with severe symptoms [22] . Zhou et al [6,p.1054–1062] also reported prolonged time till viral clearance among severe and critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our findings were similar to those of a small Japanese study of 63 patients treated at hospitals in Nara Prefecture (median age 47 [SD 19.9]). This study reported a viral clearance period of 20 days [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al, observed that the younger patients who recovered from COVID-19 took less time to clear SARS-CoV-2 compared to the elderly patients; thus, a classification of the isolation periods based on age could be considered. 8 Male 62.14% in Group1, 71.9% in Group 2, 83.3% in Group3, Female 37.8% in Group 1, 28.10% in Group 2, 16.67% in Group 3 respectively (Figure 1).…”
Section: Age Distributionmentioning
confidence: 91%